Growth rate study of Enhalus acoroides (L.f.) Royle in Talin Bay, Batangas - Hernandez, Anthony L. (Animo Repository, 1996)
The growth rate of Enhalus acoroides (L.f.) Royle at Talin Bay, Batangas, were studied from August to September, 1996. Mean Growth was 14.10 mm/day in August and 13.52 mm/day in September. The overall mean growth rate of Enhalus acoroides was 13.81 mm/day over the two-month sampling period. The minimum growth rate of Enhalus acoroides was recorded in September (8.00 mm/day) while the maximum growth rate of Enhalus acoroides recorded was in August (19.89 mm/day). The horizontal distribution pattern of Enhalus acoroides in Talin Bay, Batangas was described to be patchy with alternating areas of high and low density. Selected areas of the line intercept, within 35-85 m from the initial point had relatively abundant species of Enhalus acoroides.